Thomas Simpson (1808-1840) - Neatby, L.H. (ARCTIC, 1987)
Thomas Simpson was born in the north of Scotland and graduated from the University of Aberdeen with more than competence. He was enrolled in the service of the Hudson's Bay Company, and in the New World he exemplified the popular conception of the clever academic launched into society. He expressed the utmost contempt for his colleagues and in a letter assured his brother Alexander that his talents would secure him speedy advancement. This arrogance made him most unpopular in the service and caused George Simpson, in doubt of his kinsman's fitness to command, to appoint Chief Factor Peter Warren Dease to lead the expedition that he was planning to extend the northern coastal survey earlier initiated by John Franklin and John Richardson. Although the leadership escaped him, Thomas Simpson was made responsible for the actual survey work, an arrangement that worked admirably. . Simpson proved his zeal and adaptability on this 1837 assignment. When the boats were blocked by ice, he took to the shore to do the work on foot; on seeing that the ice had receded, he borrowed an umiak to finish the work. No one applauded his success more than himself: "Mine alone is the victory," he wrote. "Dease is an unworthy, indolent, illiterate soul." In the next season - 1838 - when an eastward thrust from Point Turnagain was halted by ice, Simpson landed and added 160 km to the map on foot. The summer of 1839 proved more friendly. They sailed through Simpson Strait, which divided King William Island from the continent, passed the estuary of Back's Fish River - to become grimly memorable 15 years later - and reached Boothia Isthmus at the mouth of the Castor and Polux River. The ruthless Simpson still did not spare the boat crews; overruling the kindly Dease, he slowed the return voyage to map parts of th south shores of King William and Victoria islands, forcing the crews to ascend the Mackenzie River in sub-zero weather with ice masses already floating downstream. . On the American prairie, Simpson met a violent death that has ...